Multi-Indel: A Microhaplotype Marker Can Be Typed Using Capillary Electrophoresis Platforms - Qu, Shengqiu; Lv, Meili; Xue, Jiaming; Zhu, Jing; Wang, Li; Jian, Hui; Liu, Yuqing; Zhang, Ranran; Zha, Lagabaiyila; Liang, Weibo; Zhang, Lin (Frontiers in Genetics, 2020)
Since the concept of microhaplotypes was proposed by Kidd in 2013, various microhaplotype markers have been investigated for various forensic purposes, such as individual identification, deconvolution of DNA mixtures, or forensic ancestry inference. In our opinion, various compound markers are also regarded as generalized microhaplotypes, encompassing two or more variants in a short segment of DNA (e.g., 200 bp). That is, a set of variants (referred to herein as multi-variants) within a certain length includes single nucleotide polymorphisms (SNP), insertion/deletion polymorphisms (Indels), or short tandem repeat polymorphisms (STRs). At present, multi-variant is mainly aimed at multi-SNPs.However, the haplotype genotyping of multi-variants relies on single-strand analysis, mainly using massively parallel sequencing (MPS).Here, we describe a method based on a capillary electrophoresis platform that can directly obtain haplotypes of individuals. Several microhaplotypes consisting of three or more Indels with different insertion or deletion lengths in the range of less than 200 bp were screened out, each of which had at least three haplotypes. As a result, the haplotype of an individual was reflected by the length of its polymorphism. Finally, we established a multiplex amplification system containing 18 multi-Indel markers that could identify haplotypes on each chromosome of an individual. The combined power of discrimination (CPD) and the cumulative probability of exclusion (CPE) were 0.999999999997234This is a provisional file, not the final typeset article and 0.9984, respectively.